ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PENJUALAN SEPEDA MOTOR YAMAHA JUPITER Z PADA PT. ALFA SCORPII PEKANBARU - Ithika Sari; Arief Rifa'i H (VALUTA, 2015)
In the trade of the product to the consumer, there are some factors that influence inselling proccess of the product. There are some factor that influence it. That factorsshould be pay attention the following criteria for example the consumer has somecriteria to buy a product. So, the the company should be create the innovation productform their competitor, the product have to special characteristic from another product.It makes the product will be interested for the consumer, and the promotion also makesthe product will be best seller. The purpose of this research is to know that the factorinfluence the volume of selling of the motorcycle merk yamaha Jupiter Z on PT. AlfaScorpii Pekanbaru. This research is quantitative and using Purposive Sampling for theconsumer and the sampel was taken by company that direct relationship with the writerwas 10 person, and for the consumer on PT. Alfa Scorpii used the Insidental Sampling.The sample define by the people who was the people that writer meet in that time. OnPT. Alfa Scorpii Pekanbaru, and the sum of the population is not defined but themaximal sum of the population is 30 People. The resulf of the research shows that thefactors that influence the volume selling of motorcycle merk Jupiter Z on PT. AlfaScorpii Pekanbaru is excelent it is indicate from the responden and the other side is notsignificant.